Ketahanan Hidup dan Fekunditas Larva Aedes aegypti (Diptera: Culicidae) Pada Habitat Suboptimal - Delfita, Rina (Sainstek : Jurnal Sains dan Teknologi, 2017)
This study aims to provide general information about the survival and fecundity of Aedes aegypti in suboptimal habitats based on relevant research articles collected from 26 journal sources. A combination of three to five keywords was used to obtain the data. This journal is obtained from four electronic data bases, namely PubMed, Medline, Scopus and Google Schoolar, which were collected during 2017. The data were obtained by identifying, screening, matching the criteria that were intended (eligibility) and reviewing those articles. There were 83 journals identified and 56 journals reviewed. In addition, there were two local journals and 52 international ones. Journal review results show that larvae are able to live and complete their development into adulthood in suboptimal habitats. Stagnant sewer water that is clear and septic tanks are suboptimal larval habitats. Phosphorus is a major limiting factor in the presence of larvae in suboptimal habitats. Thus, manipulating the phosphorus content in ditches and septic tanks is one of the vector control strategies.